Three-dimensional Thermal-hydraulic Design of Fuel Element for Small Modular Fluoride-salt-cooled High-temperature Advanced Reactor - DING Tongwei1, ZHANG Dalin2, CHEN Shuo3 (Yuanzineng kexue jishu)
The small modular fluoride-salt-cooled high-temperature reactor (FHR) has the advantages such as high thermal efficiency, and modular transportation and installation, which integrates the technological merits of the fourth-generation nuclear energy systems. The flow and heat transfer characteristics of the hot channel of fuel pin in the core is important for reactor thermal-hydraulics design and safety analysis. Focusing on the thermal-hydraulics design and safety assessment of the integral inherently safe small fluoride-salt-cooled high-temperature advanced reactor (FuSTAR), the three-dimensional numerical analyses of hot channel thermal-hydraulic characteristics in FuSTAR with four different fuel element types were carried out. The high-quality mesh generation, mesh independence check, and turbulence model comparison for helical cruciform fuel (HCF) with axial twisted geometry were carried out. Comparing with the experimental results, the maximum relative error of SST k-ω model is 7.8%, which shows the best numerical accuracy. Hence the following analyses adopted the SST k-ω model for numerical simulation. According to four candidate core design schemes, the linear power distribution of the most heated pin calculated by neutronics simulation of each core design scheme was adopted as the heat source of thermal-hydraulics calculation to make a more real thermal-hydraulics assessment, and the hot spot temperature and the pressure drop comparative analyses were conducted. The results of hot spot temperature comparative analysis show that the peak temperatures of the four design schemes are all under the temperature limit (about 1 573 K), and the HCF_TRISOC scheme has the lowest peak temperature, which is 1 145 K. The cladding temperature of HCF exhibits the periodic characteristic because of the changes of the lateral thermal conductive distance, and HCF_TRISOC scheme shows the smallest temperature difference between the fuel pellet and cladding, which maintains the most uniform temperature distribution. Therefore, HCF_TRISOC scheme has the better heat transfer ability, and it is beneficial to reduce the thermal stresses to improve the inherent safety of the reactor. The results of flow and pressure drop comparative analyses show that the HCF_UZr scheme has the largest cross-flow intensity and the smallest pressure drop, which is beneficial to strengthen heat exchange and save power of the pump. Based on the above analysis results, among the four FuSTAR schemes, the HCF_TRISOC scheme has the best heat transfer and safety performance, and it is proposed to be selected as the fuel element scheme of FuSTAR. The research results in this paper obtain a reference basis for the preliminary core design of FuSTAR, which could provide guidance for the further optimization of the core.